Isotopic carbon turnover in pig hoof and rib - Regina Maria Nascimento Augusto Blaitt; Vivian Lo Tierzo; Juliana Célia Denadai; Cibele Regina de Souza Kruliski; Carlos Ducatti; Dirlei Antonio Berto; Maria Márcia Pereira Sartori (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate the behavior of carbon incorporation and turnover in hoof and ribs of pigs at different periods of development in the search for tissues that reflect longer the former diet. We used 132 commercial hybrids (barrows and females), weaned at an average age of 21 days, distributed in a completely randomized design with four treatments on different days of substitution of corn (C4 cycle plant grain) diets with broken rice (C3 cycle plant grain) at 21, 42, 63 and 110 days of age to change the carbon-13 isotope signal. By means of isotopic dilution curves, we observed that animals whose C4 diet was replaced with C3 diet at 21, 42, 63 and 110 days of age, for hoof and rib, reached a new level of isotope equilibrium. Bone samples are better choices to reflect the former diet, due to conservation of the isotopic signal for longer.